Transition from vitreous to floury endosperm in maize (Zea mays L.) kernels is related to protein and starch gradients. (March 2016) - Gayral, Mathieu; Gaillard, Cédric; Bakan, Bénédicte; Dalgalarrondo, Michèle; Elmorjani, Khalil; Delluc, Caroline; Brunet, Sylvie; Linossier, Laurent; Morel, Marie-Hélène; Marion, Didier
Abstract: Relationships between kernel vitreousness and proteins and starch partitioning to the floury and vitreous regions of the endosperm were monitored in a set of 13 maize inbred lines. Decrease of protein contents from the vitreous to the floury endosperms were mainly assigned to α-zeins. Using Raman microspectroscopy, we observed a protein gradient from the periphery to the center of endosperms that well fitted with the inverse relationships between vitreousness and protein content of the vitreous and floury regions. In addition, Raman microspectroscopy highlighted an increase of starch crystallinity from the periphery to the center of the maize endosperms. This agrees with the higher amylose and associated lipid contents within starches of vitreous than in those of floury endosperms. Finally, starch granules from vitreous regions displayed more channels than the floury ones. These channels contain proteins that might favor adhesion of proteins to starch granules or granule–granule contacts to form the close packing of the vitreous endosperm. Therefore transition from vitreous to floury endosperm is at least the result of both protein and starch gradients. These gradients are probably associated with metabolic gradients that have been observed during endosperm development. Highlights: Zein contents decrease from endosperm periphery to the center. Starch crystallinity increases gradually from endosperm periphery to the center. Starch granules of vitreous endosperms have more channels than those of floury endosperms.